DNA quality and quantity in adipose tissue: a comparison of the effects of bomb explosion - Leonardo; Sugiharto, Ade Firmansyah; Indriatmi, Wresti; Atmadja, Djaja Surya; Yudianto, Ahmad; Herkutanto; Widodo, Wahyu (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Adipose tissue is often overlooked in DNA testing due to misconceptions about its DNA content. However, its shock-absorbing qualities may be useful for high-pressure scenarios like bomb blasts. This study aimed to evaluate DNA quality and quantity in adipose tissue affected by blasts compared to that in unaffected tissue. METHODS 10 adipose tissue samples were taken from regions near and far from the blast, representing the blast-exposed and non-blast-exposed groups. The adipose tissue was stored at a low temperature for 5 days, after which an organic extraction method was applied. The purity of the DNA extract was assessed using a NanoDrop spectrophotometer, and its integrity was evaluated using 0.8% concentration gel electrophoresis at 60 V for 90 min. DNA typing was conducted using the GlobalFiler™ kit, and DNA quantity was determined with the Quantifiler™ Trio DNA Quantification kit. RESULTS Of 20 DNA extracts from adipose tissue, all samples demonstrated purity, integrity, and complete typing results. Adequate integrity was found in 90% of samples in both groups. A 50% incidence of allele shifting was observed at the D7S820 locus within the blast-exposed group. CONCLUSIONS DNA from blast-exposed adipose tissue exhibited no significant quality or quantity differences from non-blast-exposed tissue. This suggested adipose tissue’s potential as an alternative DNA source in a bomb explosion.